Non-cirrhotic portal hypertension and pregnancy outcome - Çift, Tayfur; Gezer, Altay; Balcan, Eray; Madazlı, Rıza; Karataş, Suat (Cerrahpaşa Medical Journal, 2019)
Objectives: The aim of the present study was to evaluate complications during pregnancy and pregnancy outcome in women with non-cirrhotic portal fibrosis and portal hypertension. Methods: Eight pregnancies with non-cirrhotic portal fibrosis and portal hypertension managed in our clinic between January 1998 – December 2008 were evaluated. Results: Mean maternal age and nulliparity rate were 27.5 ± 5.2 and 50 % respectively. In two patients (2/8, 25 %) variceal bleeding during pregnancy occured. Mean gestational week of delivery and birth weight were 35.3 ±3.3 and 2525 ± 846 gram respectively. The rates of fetal growth restriction and delivery before 34 weeks gestation were 25% and 12.5% respectively. There was no maternal mortality. Perinatal mortality rate was 12.5%. Conclusion: Pregnancies with non-cirrhotic portal fibrosis should be managed with a team approach. Our results indicate that these pregnancies managed properly have good pregnancy outcomes.